Strategies for translating euphemistic expressions from African English into Arabic in "A grain of wheat" - Anber, Sameerah Jabbar (2016)
This study examines the strategies for translating euphemistic expressions from African-English into Arabic. Euphemism is a figure of speech which conceals unpleasant or sad ideas. This study aims to fulfill two main objectives; to identify translation strategies,and to examine the influence of sociocultural differences in translating euphemistic meanings in “A Grain of Wheat" from English into Arabic. Euphemism poses a significant problem in translation as it requires an accurate equivalence in the receptor’s language as well as competence of the translator in interpreting and rendering the meaning of euphemistic expressions. Inadequate translation of euphemistic expressions leads to distortion of the intended meaning and may cause inaccuracy, ineffectiveness and dysphemism in the target language. The analysis was carried out on 24 sets of euphemistic expressions taken from 136 expressions that include 49 items for death, 62 items for sex, 15 items for human body and 10 items for bodily function collected from Ngūgī’s novel "A Grain of Wheat" and its translations into Arabic by Abdul-kareem Mahfouz (1983) and Salman Hassen Al-Aqidi (1987). "A Grain of Wheat” was chosen because it is Ngūgī’s influential work that proves its mettle in realising how writing could be an instrument to progress. The novel is loaded with euphemistic expressions and cultural nuances. This study is qualitative in nature and adopted the model of Allan and Burridge (1991) on four topics encompassing death, sex, human body, and bodily function. The study employed textual analysis method based on the strategies proposed by Leppihalme (1997) and Unseth (2006). The findings showed that the rendering of euphemistic expressions seemed to be discrepant between both Arab translators. Both translators used three strategies, namely literal, omission and structure change to preserve the SL flavour and integrity. Both translators also strived to keep the meaning in the source texts sound natural by transferring the SL’s structure. Omission and literal strategy employed by the translators frequently may not express euphemistic words functionally.The findings also revealed that both translators attempted to translate semantically the euphemistic expressions but at the expense of rendering them adequately into the target culture. While the researcher found similarities and differences in the employment of translation strategies in translating the euphemistic expressions, the Syrian translation is apparently better delivered than the Iraqi translation. The findings also suggested that knowledge and competence of the translators in handling sociocultural differences as well as the employment of effective strategies such as those proposed by Leppihalme and Unseth are indispensable tools for solving the problems of translating euphemistic expressions.